THE ROLE AND IMPORTANCE OF GRAPHIC REPRESENTATION IN THE ACTIVITIES OF FUTURE DESIGNERS - Berdiyev Nurmon Ochilovich (Journals Park Publishing, 2023)
This article delves into the crucial role that graphic representation plays in the activities of future designers. With a focus on the evolving landscape of design, we explore the various dimensions of graphic representation, its impact on communication and creativity, and its significance in shaping the work of designers. The article combines literature analysis, a discussion of methods, presentation of results, and a thorough examination of implications to provide a comprehensive understanding of the subject.
Keywords: Graphic representation, design, future designers, visualization, communication, creativity.